2022
DOI: 10.3389/fphys.2022.870154
|View full text |Cite|
|
Sign up to set email alerts
|

Both caffeine and Capsicum annuum fruit powder lower blood glucose levels and increase brown adipose tissue temperature in healthy adult males

Abstract: Using a combination of respiratory gas exchange, infrared thermography, and blood glucose (BGL) analysis, we have investigated the impact of Capsicum annuum (C. annuum) fruit powder (475 mg) or caffeine (100 mg) on metabolic activity in a placebo controlled (lactose, 100 mg) double-blinded three-way cross-over-design experiment. Metabolic measurements were made on day 1 and day 7 of supplementation in eight adult male participants (22.2 ± 2 years of age, BMI 23 ± 2 kg/m2, x̅ ± SD). Participants arrived fasted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…This is consistent with an increase in lipids and fatty acids in responders (compared with non-responders) in our study. Therefore, in our study, it is possible that caffeine metabolism could have altered the effectiveness of exercise in responders, thus enabling them to lose more weight, while also enhancing biological pathways that further promoted weight loss [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with an increase in lipids and fatty acids in responders (compared with non-responders) in our study. Therefore, in our study, it is possible that caffeine metabolism could have altered the effectiveness of exercise in responders, thus enabling them to lose more weight, while also enhancing biological pathways that further promoted weight loss [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The subjects underwent, before and after exposure, both 18F-FDG PET and indirect calorimetry, in order to assess the total energy expenditure. The results showed that capsinoids increased energy expenditure in BAT-positive participants and, when combined with cold, increased fat oxidation, improved insulin sensitivity and increased HDL-cholesterol [58,59].…”
Section: Capsaicin and Capsinoidsmentioning
confidence: 99%
“…Furthermore, nutritive aspects can modulate its function. While capsaicin, caffeine (Van Schaik et al, 2022), rutin (Cheng et al, 2022) or unsaturated long chain fatty acids (Fosch et al, 2023) stimulate the BAT thermogenesis, food additives or pesticides (Wang et al, 2021) as well as saturated fat (Fosch et al, 2023) can inhibit the thermogenesis in BAT.…”
Section: Physiology Of Human Batmentioning
confidence: 99%